Long-Term Population Dynamics of Large Raptors in the Important Bird Area “Kamsko-Bakaldinskiye Marshes” (Nizhny Novgorod Region) - Sergei V. Bakka; Nadezhda Yu. Kiseleva; Pavel M. Shukov (Пернатые хищники и их охрана)
Identification of breeding territories and long-term population monitoring has been carried out in the Important Bird Areas (IBA) with a global importance “Kamsko-Bakaldinskiye marshes” since 1980. Five large bird species were studied here: Osprey (Pandion haliaetus), Short-Toed Eagle (Circaetus gallicus), Greater Spotted Eagle (Aquila [Clanga] clanga), Golden Eagle (Aquila chrysaetos), White-Tailed Eagle (Haliaeetus albicilla). In this report we will summarize the results.